The value of emptiness: MUJI’s strategies - Petitimbert, Jean-Paul (Revista Acta Semiotica, 2021)
Setting the scene 1. Advertising emptiness 2. Designing emptiness 3. Going further : ethics and æsthetics 4. Ways of doing — ways of being Conclusion